Ácido cítrico como promotor de crescimento para codornas - Nunes, Adriano Silva (2016)
The studies about the use of antimicrobials has been intensified, due to the possibility of these antimicrobials being the cause of bacterial tolerance in human beings that consume products of animal origin. The organic acids stand out among the natural antimicrobials, performing similar effects to convencionals antimicrobials. Although, the citric acid stands out as a potential natural antimicrobial. Because the coturniculture follow the same trend of the poultry industry, which is growing, to keep production levels in farming systems to meet the market demand, the use of antimicrobials is necessary. Therefore, it is necessary to evaluate the effects of different levels of citric acid as a growth promoter in Japanese quail diets. To achieve this, a sensibility analysis was realized to verify if citric acid has the capacity to inhibit the bacterial growth of Eschrichia coli and Salmonella spp in vitro, and a field test to further examine its effects on the Japanese Quails' digestive tract bacterial growth, evaluate the impact the citric acid has on the manifestation of genes related to nutrients transportation, and intestinal antioxidant capacity; so that the adequate level of citric acid integration can be determined. The in vitro testing was realized utilizing three levels of citric acid (0,0%; 0,6% and 1,2%) to verify its impact on Eschrichia coli and Salmonella spp , which was none. The performance test was realized utlizing 450 nine days old quails divided in total random design with five treatments, nine iterations and 10 birds per unit. Was inert added so to keep the diets isoenergetic and isoproteinicm getting five levels of citric acid: 0,0; 0,3; 0,6; 0,9; and 1,2%. The trials spanned 35 dias and the testing protocols were approved by the ethics comitee. The citric acid had a impact on growth (P=0,01), feed conversion (P=0,05), as well as manifestation of the genes SGLT1 (P=0,01), GPX7 (P=0,01), and SOD (P=0,01). In conclusion, the citric acid did not inhibit Eschrichia coli and Salmonella spp growth in the in vitro tests; improves the manifestation of aminoacids transporter and Sodiumglucose cotransporter 1. The best citric acid level for growing laying quails diet is of 0,60%.